Development of Local Culture-Based Tpack E-Books Improves Creativity & Cultural Literacy of Elementary School Students - Sofiana, Nurma; Alfi, Cindya; Fatih, Mohamad (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
Science learning, especially on social science-based materials, has an important role in instilling character, social skills, and cultural understanding from an early age. However, in practice, social studies learning in elementary schools is still dominated by the use of printed and abstract teaching materials, which is reinforced by the researcher's findings where limited use of technology still occurs in the learning process at SDN Sumberjo 1. This study aims to develop and test the validity, feasibility, and effectiveness of local culture-based e-books with the TPACK approach on the cultural diversity material of science for grade IV SDN Sumberjo 1, Blitar Regency. The research method used is RnD with the ASSURE model through the stages of needs analysis, formulation of objectives, selection of media and materials, limited trials, expert validation, and product evaluation and revision. Data were collected through interviews, observations, questionnaires, and pretest-posttest tests and then analyzed qualitatively and quantitatively using the N-Gain test. The results of the validation by material, language, and media experts showed an average percentage of 92.15% with a very valid category, while the feasibility test obtained an average of 92.19% with a very feasible category. The implementation of e-books resulted in an increase in creativity with an N-Gain of 0.60 and cultural literacy of 0.57, which is considered moderate. These findings indicate that local culture-based e-books are quite effective in supporting contextual learning while simultaneously enhancing students' creativity and cultural literacy in elementary school learning environments in an optimal, sustainable manner.